P-DOPED COFFEE GROUND-DERIVED HARD CARBON FOR BOOSTING SODIUM-ION BATTERIES - Kalibek, Madina; Konarov, Aishuak; Bakenov, Zhumabay (National Laboratory Astana, 2022)
The paper proposed the facile and successful preparation of P-doped coffee ground-derived hard carbon using H3PO4 as a dopant material for sodium-ion batteries. The manipulation with 1-3 M of H3PO4, contributed to finding the optimal concentration for the maximum incorporation of phosphorus ions into the carbon framework. The use of 2 M of H3PO4 dopant material for hard carbon as anode for sodium-ion battery delivers promising electrochemical performance
Keywords: Type of access: Embargo; P-doped coffee ground-derived hard carbon; sodium-ion batteries